Pengembangan Instrumen Pewarnaan Alam pada Studio Wastra Pinankabu - Muhammad Ilhamdi Rusydi; Prima Fithri; Haznam Putra; Andi Pawawoi; Muhammad Imran Hamid; Riko Nofendra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
One of the obstacles the Pinankabu studio faces is the lack of adequate equipment for processing silk threads and the currently available dyeing equipment for natural dyeing. Some equipment such as degumming pans, hangers, furnaces, and stoves are no longer suitable for needs. The properties of silk, which vary with demand and temperature, must be studied under appropriate conditions. Currently, partners can not confirm whether these conditions are met at work. The planned solution to this problem is the design of degumming pans, hangers, furnaces, and stoves that can increase work effectiveness and improve the quality of production and design systems to measure pH and temperature accurately and in real-time. This activity aims to develop yarn processing equipment at Pinankabu studio to increase productivity and maintain product quality. The expected benefits of this activity are that partners have natural colouring instruments that can improve the quantity and quality of production. Operators can work comfortably because the equipment is designed to design ergonomic users. Equipment that will be developed is an example of a similar business. The method used was the implementation of engineered products on partners. The implementation stages consisted of problem formulation, solution determination, solution design, implementation, evaluation, and activity outputs. The expected result is that partners can increase the productivity and quality of the yarn produced.